The Presence of Sustainability in Hungarian Geography Textbooks - Janos Varjas (European Journal of Geography)
The Lucerne Declaration on Geographical Education for Sustainable Development recommends including the subjects of Education for Sustainable Development and sustainability in Geography teaching all over the world. One possible way to examine the practical implementation of education for sustainability is through textbook analysis. The present study investigates how Hungarian textbooks published after 2015 perform in terms of ESD. In order to do that, it conducts content analysis the help of the MAXQDA 2020 programme, looking for the presence of Sustainable Development Goals and competencies related to sustainability in the analysed educational media. The results show that Geography in Hungary has an ecological approach to teaching about sustainable development. Sustainability issues relevant to society are less emphasized. Textbooks written in a modern, problem-centric spirit pay a lot of attention to competence development. However, ESD only appears in the studied textbooks sporadically; there is no evident competence development concept present in them in a planned, structured format.